2022
DOI: 10.1007/s43545-022-00368-x
|View full text |Cite
|
Sign up to set email alerts
|

Learning ability of top university students in China: Shanghai Jiao Tong University as a case study

Abstract: The network illustrates the interrelationships among diverse entities and has attracted considerable attention. A wide range of applications makes the network a popular modeling tool, including but not limited to social networks [1], business administration [2], and city construction [3]. In these fields, quantifying network value is essential. By examining network value, companies gain insights into consumer behavior, allowing them to refine marketing strategies accordingly [4]. Similarly, investigating netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 278 publications
(501 reference statements)
0
2
0
Order By: Relevance
“…Engin analyzed the influence of climatic factors such as wind, rain, humidity, and sunshine on the dwellings in the eastern part of the Black Sea [32]. Similar research was conducted on vernacular dwellings in the desert of West Africa [33], rammed earth buildings in Spain [34], rural vernacular dwellings in coastal, lowland, and mountainous areas of Cyprus [35], vernacular dwellings in Taiwan [36], vernacular dwellings in Vietnam [37], vernacular buildings in a hot arid area of Iran [38], and dwellings in northern Jiangsu, China [39]. All these studies focused on vernacular dwellings in different regions from a microscopic perspective.…”
Section: Research On the Formation And Performance Of Vernacular Dwel...mentioning
confidence: 75%
“…Engin analyzed the influence of climatic factors such as wind, rain, humidity, and sunshine on the dwellings in the eastern part of the Black Sea [32]. Similar research was conducted on vernacular dwellings in the desert of West Africa [33], rammed earth buildings in Spain [34], rural vernacular dwellings in coastal, lowland, and mountainous areas of Cyprus [35], vernacular dwellings in Taiwan [36], vernacular dwellings in Vietnam [37], vernacular buildings in a hot arid area of Iran [38], and dwellings in northern Jiangsu, China [39]. All these studies focused on vernacular dwellings in different regions from a microscopic perspective.…”
Section: Research On the Formation And Performance Of Vernacular Dwel...mentioning
confidence: 75%
“…Chen et al [13] adopted high-speed schlieren visualisation and phase-locked PIV technology to study the flow fields generated by different frequency acoustic excitations and discovered that they have different degrees of influence on the mode and brightness of the diffusion flame. Wang [14] used PIV technology to find the velocity of the combustion field in a combustion chamber and found that the laser energy, cross-frame time, and other factors affected the experimental results. The PIV technology was first proposed by Adrian [11] in the 1980s.…”
Section: Introductionmentioning
confidence: 99%